2022
DOI: 10.3389/fcimb.2022.824547
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas sobria Serine Protease Degrades Several Protein Components of Tight Junctions and Assists Bacterial Translocation Across the T84 Monolayer

Abstract: Aeromonas sobria is a Gram-negative pathogen that causes food-borne illness. In immunocompromised patients and the elderly, A. sobria opportunistically leads to severe extraintestinal diseases including sepsis, peritonitis, and meningitis. If A. sobria that infects the intestinal tract causes such an extraintestinal infection, the pathogen must pass through the intestinal epithelial barrier. In our earlier study using intestinal cultured cells (T84 cells), we observed that an A. sobria strain with higher A. so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Impairs host immune function Gurkok and Ozdal ( 2021 ); Papulzai et al ( 2020 ) eno Enolase Glycolytic enzyme which binds to human plasminogen on cell surfaces leading to cancerous conditions, neurological disease, and autoimmunity Sha et al ( 2003 ) ser/ahp Serine protease Aids in invasion by breaking down host proteins. Evasion of the immune system by deactivating specific components Feng et al ( 2022 ); Ueda et al ( 2022 ) Structural components Flagella Polar and lateral Plays roles in biofilm formation, motility, and enterocyte adhesion, and promotes colonization and invasion Cheng et al ( 2023 ); Lau et al ( 2023 ) A-layer Outer layer protein array An array of tetragonal proteins, known as A-protein, which is tethered to the cell by LPS. Provides protection against immune defenses such as serum-mediated killing and macrophage cytotoxicity Mendoza-Barberá et al ( 2021 ); Paquet et al ( 2019 ) Capsule Outer layer of polysaccharides Aids in host colonization and invasion; prevents phagocytosis by host macrophages Heiss et al ( 2019 ); Mendoza-Barberá et al ( 2021 ) Fimbriae/Pilli Filamentous structures on the bacterial surface that aid in adhesion.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Impairs host immune function Gurkok and Ozdal ( 2021 ); Papulzai et al ( 2020 ) eno Enolase Glycolytic enzyme which binds to human plasminogen on cell surfaces leading to cancerous conditions, neurological disease, and autoimmunity Sha et al ( 2003 ) ser/ahp Serine protease Aids in invasion by breaking down host proteins. Evasion of the immune system by deactivating specific components Feng et al ( 2022 ); Ueda et al ( 2022 ) Structural components Flagella Polar and lateral Plays roles in biofilm formation, motility, and enterocyte adhesion, and promotes colonization and invasion Cheng et al ( 2023 ); Lau et al ( 2023 ) A-layer Outer layer protein array An array of tetragonal proteins, known as A-protein, which is tethered to the cell by LPS. Provides protection against immune defenses such as serum-mediated killing and macrophage cytotoxicity Mendoza-Barberá et al ( 2021 ); Paquet et al ( 2019 ) Capsule Outer layer of polysaccharides Aids in host colonization and invasion; prevents phagocytosis by host macrophages Heiss et al ( 2019 ); Mendoza-Barberá et al ( 2021 ) Fimbriae/Pilli Filamentous structures on the bacterial surface that aid in adhesion.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…The mechanical barrier, also known as the physical barrier, depends on the structures of the intestinal epithelium, lamina propria, and muscular mucosae. 11 The intestinal epithelium is composed of several cell types, including Enterocytes, Goblet Cells, Paneth Cells, Cupped Cells, Enteroendocrine Cells, Microfold (M) cells, and tuft cells, 12 collectively referred to as intestinal epithelial cells (IECs). 13 An important role of IECs is to maintain intestinal barrier integrity, which allows solvent, electrolytes, and nutrients to pass through and impedes access to pathogens.…”
Section: The Intestinal Barrier and Bacterial Translocationmentioning
confidence: 99%
“… 70 Aeromonas sobria serine protease (ASP), secreted by A. sobria , degrades tight junction components including ZO-1, 2, 3, and claudin-7, and facilitates bacterial translocation through the intestinal epithelial cell line, T84. 11 In addition, ASP destroys components including nectin-2 and afadin. 71 Haderer et al 72 reported that a novel bacterial protease produced by Escherichia coli and Proteus mirabilis in patients with spontaneous bacterial peritonitis was responsible for the cleavage of E-cadherin structures.…”
Section: Mechanisms Of Bacterial Translocationmentioning
confidence: 99%
“…Other pathogens can activate intracellular host proteases or promote their expression and secretion to benefit bacteria in a tightly regulated spatiotemporal manner to ensure a safely replication niche and efficient dissemination ( Bergounioux et al., 2012 ). Bacterial proteases can also directly target AJC proteins for degradation, such as tight junction-membrane protein claudins in Aeromonas and Campylobacter infections ( Sharafutdinov et al., 2020 ; Ueda et al., 2022 ). Several leptospiral proteases capable of degrading extracellular matrix or complement factors were identified by experimental and in silico studies ( Daroz et al., 2020 ; Daroz et al., 2021 ; Courrol et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%